1995
DOI: 10.1128/aem.61.11.3919-3927.1995
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of an extracellular H2O2-dependent ligninolytic activity of the white rot fungus Pleurotus ostreatus in the decolorization of Remazol brilliant blue R

Abstract: During solid-state fermentation of wheat straw, a natural lignocellulosic substrate, the white rot fungus Pleurotus ostreatus produced an extracellular H 2 O 2-requiring Remazol brilliant blue R (RBBR)-decolorizing enzymatic activity along with manganese peroxidase, manganese-independent peroxidase, and phenol oxidase activities. The presence of RBBR was not essential for the production of RBBR-decolorizing enzymatic activity by P. ostreatus, because this activity was also produced in the absence of RBBR. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(35 citation statements)
references
References 56 publications
0
34
0
1
Order By: Relevance
“…RBBR decolorization assay-H 2 O 2 -dependent decolorization of certain dyes can indicate oxidoreductive enzyme activity; for example, RBBR has been used for peroxidases in fungi (Glenn and Gold 1983;Pasti and Crawford 1991;Vyas and Molitoris 1995). We tested small volumes of gut fluid for peroxidase-like activity by incubating a RBBR solution and activating it with H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…RBBR decolorization assay-H 2 O 2 -dependent decolorization of certain dyes can indicate oxidoreductive enzyme activity; for example, RBBR has been used for peroxidases in fungi (Glenn and Gold 1983;Pasti and Crawford 1991;Vyas and Molitoris 1995). We tested small volumes of gut fluid for peroxidase-like activity by incubating a RBBR solution and activating it with H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The results revealed that low (less than 0.5 µM) and also high (over 2 µM) H 2 O 2 production decreased the decolorization capacity for both dyes tested. VYAS and MOLITORIS (1995) also demonstrated an inhibition effect of high concentrations of H 2 O 2 on decolorization of RBBR in P. ostreatus. Our results showed that fungi producing H 2 O 2 in the concentration range 1.0 -1.5 µM exhibited the highest decolorization capacity.…”
Section: Resultsmentioning
confidence: 78%
“…-Decolorisation of RBBR was estimated in a medium using 0.005% of RBBR according to VYAS and MOLITORIS [6]. In parallel, it was also detected after 1-2 weeks of growth of plants on agar media containing 0.02% of RBBR.…”
Section: Estimation Of Enzyme Activitiesmentioning
confidence: 99%